PENGARUH TEMPER TANTRUM TERHADAP LINGKUNGAN BELAJAR ANAK DI PAUD AL-AMIN HARUN TALUN CIREBON - Saarah Shafa Salsabila; Septi Gumiandari (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Temper tantrums are an emotional behavior that is often experienced by children at an early age. This behavior can affect children's learning environment in Early Childhood Education (PAUD). This research aims to identify the influence of temper tantrums on children's learning environment at PAUD Al-Amin Harun Talun. Data was collected through observation and interviews with PAUD teachers and children's parents. Data analysis was carried out using quantitative survey or questionnaire research methods. The results of this research show that temper tantrums can affect children's learning processes, social interactions, learning atmosphere, and the welfare of teachers and staff at PAUD Al-Amin Harun Talun.